2019
DOI: 10.48550/arxiv.1902.03950
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Equivalent Polyadic Decompositions of Matrix Multiplication Tensors

Abstract: Invariance transformations of polyadic decompositions of matrix multiplication tensors define an equivalence relation on the set of such decompositions. In this paper, we present an algorithm to efficiently decide whether two polyadic decompositions of a given matrix multiplication tensor are equivalent. With this algorithm, we analyze the equivalence classes of decompositions of several matrix multiplication tensors. This analysis is relevant for the study of fast matrix multiplication as it relates to the qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…It was observed in [5] that the matrices H r defined in (31) are similar to H ′ r computed for A ′ , B ′ , C ′ , see (35). The similarity of the two matrices implies that the matrices have the same characteristic polynomial [25].…”
Section: B Generalized Signaturementioning
confidence: 86%
See 3 more Smart Citations
“…It was observed in [5] that the matrices H r defined in (31) are similar to H ′ r computed for A ′ , B ′ , C ′ , see (35). The similarity of the two matrices implies that the matrices have the same characteristic polynomial [25].…”
Section: B Generalized Signaturementioning
confidence: 86%
“…It was also noted in [5] that if an integer-valued decomposition exists, its generalized signature should be integer-valued as well. However, we observed that many times, the matrices H r have a low rank, and the higher elements of the generalized signature are zeros, and do not help to distinguish different decompositions.…”
Section: B Generalized Signaturementioning
confidence: 99%
See 2 more Smart Citations
“…Notwithstanding the problems of defining algorithms and the undecidability of gauging equality (much less computing a principled similarity) of algorithms in general, Dowker homology can capture salient information about straight-line or basic block algorithms. 8 In this restricted setting, it is not hard to identify various narrow classes of algorithms that admit reasonable definitions.…”
Section: Dowker Homology To Analyze Complexity Of Source and Binary Codementioning
confidence: 99%